Six ways to maximize survey response rates: lessons from a medical school accreditation survey in a Canadian setting - Arshia Pedram Javidan; Yeshith Rai; Jeffrey Cheung; Raumil V Patel; Kulamakan Mahan Kulasegaram (Canadian Medical Education Journal, 2023)
Background: Surveys are being increasingly used to gather feedback and study data in healthcare professions. However, it may be challenging to achieve high response rates in surveys administered to healthcare professionals. The aim of this paper is to report six strategies that contributed to a high response rate on the Independent Student Analysis at the University of Toronto (U of T), which can be applied to other surveys to achieve strong response rates amongst healthcare professionals.